Effects of light on the photobiology and growth of the commercially valuable macroalgae Codium tomentosum - Marques, Rúben Filipe Nascimento (2021)
Portugal has approximately 950 km of a coastline with a high diversity of macroalgal species, most of them edible and commercially valuable. Macroalgae are becoming reliable sources of nutritional supplements and bioactive compounds. Thus, an increase in demand for these organisms requires sustainable seaweed aquaculture alternatives to produce algal biomass rather than exploiting natural resources. The company ALGAplus was pioneer in taming Codium tomentosum. Currently, this macroalgae is produced in integrated multitrophic aquaculture earth pond systems designed by ALGAplus, and mainly commercialized for food and cosmetics. This macroalgae is a source of valuable bioactive compounds used for health care (antioxidant, antitumor, hypoglycemic) and has a high nutritional value (rich in polyunsaturated fatty acids and vitamin A) causing an increasing consumer demand, and therefore a necessity for the optimization of C. tomentosum production. In this project, C. tomentosum produced by ALGAplus, was studied to determine the best conditions for this algae cultivation, considering effects on growth and photobiology at a nursery scale production. In the first phase of this work, different temperatures (13 ºC and 17 ºC) and different photoperiods (long-day and short-day) were evaluated. The second part aimed at assessing the variations in growth and productivity, in photosynthetic activity and photosynthetic pigments concentrations, of exposing C. tomentosum cultures to different light qualities with selected wavelengths (White, Blue and Red). The literature for this species, regarding growth conditions and photobiology is scarce. Therefore, this work aims to fill the gaps of knowledge regarding C. tomentosum photophysiology optimizing culturing protocols. The macroalga C. tomentosum showed higher growth rates when exposed to the long photoperiod, and no significant differences between temperatures. However, the photosynthetic activity evaluated by steady-state light curves, estimated from variable chlorophyll a measurements, was higher at the lower temperature tested. The pigment profile did not show significant changes between treatments, however there was an increase of pigment concentrations in the long photoperiod treatment. Photoperiod had also a ratio change on the carotenes identified, the presence of ε-carotene under short photoperiod and β-carotene under long photoperiod. The macroalga C. tomentosum showed lower productivity under blue light, concomitant with a considerable growth of green microalgae. At the end of the experimental period, the photosynthetic performance was similar between the different spectra. The photosynthetic pigment profiles (chlorophyll a and b, siphonoxanthyn e siphonein) showed increased concentrations under blue light, possibly as a result of competition for the available light with microalgae. The remaining spectral conditions (Red and White light) presented similar pigment concentrations. In conclusion, C. tomentosum achieved higher growth rates at long-day photoperiod. The use of red or white light is advised to control the growth of microalgal contaminations and to optimize growth.